Neurofibromatosis type II presenting as vertical diplopia - (:unkn) unknown (My University, 2004)
Neurofibromatosis type II (NF II) is rare and most commonly presents with hearing loss, tinnitus and/or vestibular disturbance in the third decade of life. The authors describe a rare case presenting with NF II with vertical diplopia due to IVth nerve palsy. The patient was otherwise asymptomatic despite multiple extensive lesions on MRI.
Keywords: Meningioma; Neurofibromatosis type II; Papilledema; Schwannoma; Vertical diplopia